“No meio do Pitiú”: diversidade e antiguidade de sambaquis amazônicos - Silva, Ana Caroline Sousa da (2022)
The objective of this work is to discuss the antiquity and diversity of the sambaquis identified until today in the Amazon and its long-term history, from the concepts of historical ecology, the modification of the landscape, and the relationships between the populations that were building these sambaquis. We will seek to reflect on the similarities and differences (geographical and material) of these sambaquis based on the bibliography available in the historical and research reports of these sites. The methodology used is a bibliographic survey of files, field diaries and reports (sometimes unpublished) that were found in museums and on the internet. From this compilation of data, we carried out a new mapping showing the location of the sites and presented a summary of the geographic position, the extension of the site (when this information is available), the chronology, the cultural material and the state of conservation of the sambaquis. amazon. The work was structured as follows: (1) research history of sambaquis in Brazilian regions, (2) Methods carried out in the research (3) characterization of these sambaquis by regions of the Amazon, (4) discussion that will be divided into two topics: a) the sambaquis as transformations in the landscape, b) preservation of the sites nowadays and Final Considerations.